T-Cell Lymphoblastic Lymphoma in a Child Presenting as Rapid Thyroid Enlargement - Shintaro Yoshihara; Muneo Nakaya; Tomoya Ichikawa (Case Reports in Otolaryngology)
The majority of lymphomas of the head and neck in children present as an enlarged cervical lymph node; however, malignant lymphoma arising from the thyroid gland is extremely rare. We report a case of a 12-year-old child who was admitted to our hospital because of a history of rapidly progressive anterior neck swelling. Histopathological studies revealed this case to be T-cell lymphoblastic lymphoma. We performed chemotherapy and the patient has kept recurrence-free survival for 18 months after the beginning of the treatment. This is the 2nd case of T-cell lymphoblastic lymphoma in the thyroid gland in a child.